Resident interactions when affirming and correcting peers in a therapeutic community for women. Issue 4 (26th November 2021) - Warren, Keith Leverett; Doogan, Nathan; Wernekinck, Uwe; Doherty, Fiona Claire
Abstract : Purpose: While recent years have seen a number of studies of social networks in therapeutic communities (TCs) and other residential settings, these have primarily focused on male residents. This paper aims to conduct a longitudinal social network analysis of interpersonal interactions in a TC for women. Design/methodology/approach: The data consists of a longitudinal directed social network of instances of feedback between 56 residents of a 16 bed TC for women over a period of 611 days. Mean age of the participants was 33.1 years, mean length of stay was 133.9 days and 91% of the participants were female. Feedback consisted of written affirmations for prosocial behavior and written corrections for contravening TC norms. Data was analyzed using a latent factor longitudinal social network model. Findings: Residents react to peer intervention in complex ways. Residents reciprocated affirmations (B = 0.14, 95% confidence interval = 0.10, 0.18) and corrections (B = 0.20, 95% CI = 0.13, 0.25). Controlling for reciprocity, participants who received affirmations were more likely to affirm and correct peers (B = 0.10, 95% CI = 0.06, 0.15; B = 0.17, 95% CI = 0.10, 0.23), suggesting that the encouragement offered by affirmations leads to increased activity. Homophily by admission time occurred in both affirmations and corrections (B = 0.23, 95% CI = 0.10, 0.37; B = 0.51, 95% CI = 0.29, 0.74). Originality/value: While affirmations and corrections serve as vehicles for behavioral reinforcement and social learning, they also allow residents to interact in ways that strengthen social bonds.